Implementing and operating net zero buildings in South Africa - Rolien Terblanche; Cameron May; Jake Steward (Buildings & Cities, 2025)
A total of 34 buildings in South Africa (ZA) have received a net zero certification between 2017 and 2023. These buildings are becoming more crucial to combatting climate change due to the reduced carbon emissions and resource efficiencies in net zero buildings (NZBs). However, in ZA, the uptake is low and slow. This study investigates the motivators and challenges of implementing and operating NZBs in ZA. Although the literature provides an insight into the motivators and challenges on a macro-scale in developed countries, these studies overlook the unique drivers and barriers faced in a micro-scale and developing countries. Semi-structured interviews with five built-environment specialists were conducted. The motivators to implement NZBs include environmental sustainability, energy-efficient systems, a reduction in the carbon footprint, viability due to long-term savings, limited natural resources, regulations, demand, global awareness and technological advancements. The motivators to operate NZBs include tenant demand and reduction in operating costs. Challenges to implement NZBs include high interest rates, a lack of awareness and education among stakeholders, a carbon-intensive energy grid, lack of tenant engagement and the grid’s inability to support privately generated electricity to be distributed to other consumers. The challenges to operate NZBs include high operating costs, complex operating manuals and a lengthy payback period. Practice relevance The findings of this study can be used in the ZA real estate development industry to broaden knowledge about the topic and to spark motivation for the implementation of NZBs. While there is currently limited knowledge in the industry, ZA is moving steadily in the direction of NZBs. These buildings offer a saving in the long run in terms of operating costs, they cater for the upcoming marked demand, and promise uninterrupted power and water supplies. It is well worth it for the industry to be educated on the matter and to invest. The technological advancement in the industry creates the opportunity for workshops to educate implementation and maintenance teams. Furthermore, a gap has been created that tertiary institutions need to address.